The efficacy of self-exercise in a patient with cervicogenic dizziness: A randomized controlled trial - Piromchai, Patorn; Toumjaidee, Nattaporn; Srirompotong, Somchai; Yimtae, Kwanchanok (Frontiers in Neurology, 2023)
Background Cervicogenic dizziness is a clinical syndrome characterized by neck pain and dizziness. Recent evidence suggested that self-exercise could improve a patient's symptoms. The objective of this study was to evaluate the efficacy of self-exercise as an add-on therapy in patients with non-traumatic cervicogenic dizziness. Methods Patients with non-traumatic cervicogenic dizziness were randomly assigned to the self-exercise and control groups. The self-exercise group was instructed to perform muscle, mobilization, and oculomotor training at home while there was no specific training given to the control group. The neck pain, dizziness symptoms, and their impact on daily life were evaluated by the Dizziness Handicap Inventory (DHI) scale, the Neck Disability Index (NDI) scale, and the visual analog scale (VAS). The objective outcomes included the range of motion test of the neck and the posturography test. All outcomes were evaluated at 2 weeks after the initial treatment. Results A total of 32 patients participated in this study. The average age of the participants was 48 years. The DHI score of the self-exercise group after the treatment was significantly lower when compared to the control group [mean difference (MD) 25.92 points, 95% CI 4.21–47.63, p = 0.021]. The NDI score after treatment was also significantly lower in the self-exercise group (MD 6.16 points, 95% CI 0.42–11.88, p = 0.036). However, there was no statistical difference in the VAS score, the range of motion test, and the posturography test between the two groups (p > 0.05). No significant side effects were noted in either of the groups. Conclusion Self-exercise is effective in reducing dizziness symptoms and its impact on daily life in patients with non-traumatic cervicogenic dizziness.